Cold Versus Hot Snare Endoscopic Resection of Large Nonpedunculated Colorectal Polyps: Randomized Controlled German CHRONICLE Trial - Steinbrück, Ingo; Ebigbo, Alanna; Kuellmer, Armin; Schmidt, Arthur; Kouladouros, Konstantinos; Brand, Markus; Koenen, Teresa; Rempel, Viktor; Wannhoff, Andreas; Faiss, Siegbert; Pech, Oliver; Möschler, Oliver; et al. (Gastroenterology, 2024)
Background & Aims - Endoscopic mucosal resection (EMR) is standard therapy for nonpedunculated colorectal polyps ≥20 mm. It has been suggested recently that polyp resection without current (cold resection) may be superior to the standard technique using cutting/coagulation current (hot resection) by reducing adverse events (AEs), but evidence from a randomized trial is missing. - Methods - In this randomized controlled multicentric trial involving 19 centers, nonpedunculated colorectal polyps ≥20 mm were randomly assigned to cold or hot EMR. The primary outcome was major AE (eg, perforation or postendoscopic bleeding). Among secondary outcomes, major AE subcategories, postpolypectomy syndrome, and residual adenoma were most relevant. - Results - Between 2021 and 2023, there were 396 polyps in 363 patients (48.2% were female) enrolled for the intention-to-treat analysis. Major AEs occurred in 1.0% of the cold group and in 7.9% of the hot group (P = .001; odds ratio [OR], 0.12; 95% CI, 0.03-0.54). Rates for perforation and postendoscopic bleeding were significantly lower in the cold group, with 0% vs 3.9% (P = .007) and 1.0% vs 4.4% (P = .040). Postpolypectomy syndrome occurred with similar frequency (3.1% vs 4.4%; P = .490). After cold resection, residual adenoma was found more frequently, with 23.7% vs 13.8% (P = .020; OR, 1.94; 95% CI, 1.12-3.38). In multivariable analysis, lesion diameter of ≥4 cm was an independent predictor both for major AEs (OR, 3.37) and residual adenoma (OR, 2.47) and high-grade dysplasia/cancer for residual adenoma (OR, 2.92). - Conclusions - Cold resection of large, nonpedunculated colorectal polyps appears to be considerably safer than hot EMR; however, at the cost of a higher residual adenoma rate. Further studies have to confirm to what extent polyp size and histology can determine an individualized approach. German Clinical Trials Registry (Deutsches Register Klinischer Studien), Number DRKS00025170.